2016
DOI: 10.1161/atvbaha.116.307294
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Novel Genome-Wide Association Study Signal in SMAD3 That Confers Protection From Coronary Artery Disease

Abstract: Objective-A recent genome-wide association study meta-analysis identified an intronic single nucleotide polymorphism in SMAD3, rs56062135C>T, the minor allele (T) which associates with protection from coronary artery disease. Relevant to atherosclerosis, SMAD3 is a key contributor to transforming growth factor-β pathway signaling. Here, we seek to identify ≥1 causal coronary artery disease-associated single nucleotide polymorphisms at the SMAD3 locus and characterize mechanisms whereby the risk allele(s) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…27) Turner et al found that SMAD3 knockdown in human arterial smooth muscle cells increased cell viability, which was consistent with an anti-proliferative role of SMAD3. 28) The increased mir-3162-3p in UA elderly patients might down-regulate SMAD3, resulting in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…27) Turner et al found that SMAD3 knockdown in human arterial smooth muscle cells increased cell viability, which was consistent with an anti-proliferative role of SMAD3. 28) The increased mir-3162-3p in UA elderly patients might down-regulate SMAD3, resulting in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the functional role of SNPs found within noncoding intergenic or intronic regions can be challenging. Previous studies have determined that intergenic SNPs often participate in regulation of proximal gene expression either by the generation of a novel enhancer element or by interacting with a preexisting enhancer element (49,50). Unlike promoters, distal enhancers are often cell type-specific, leading to tissue-specific risk SNP effects (51).…”
Section: Discussionmentioning
confidence: 99%
“…Other notable CAD-related functional studies include one by Turner et al, 23 where genetic and epigenetic fine-mapping were used to identify a causal SNP in intron 1 of SMAD3, rs17293632. Using chromatin immunoprecipitation and small interfering RNA-induced knockdowns, these investigators demonstrated that the rs17293632-T allele plays a protective role by disrupting a consensus AP (activator protein)-1 binding site in the SMAD enhancer region, reducing the activity of the enhancer and in turn, SMAD3 expression.…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%